Information extraction with active learning : a case study in legal text - Cardellino, Cristian Adrián; Villata, Serena; Alonso i Alemany, Laura; Cabrio, Elena (2022)
Fil: Cardellino, Cristian Adrián. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.